FACTORS AFFECTING ENTREPRENEURSHIP INTEREST IN “KURASA” STUDENT ENTERPRISE OF UNISBA BLITAR - Nurul Farida (JARES (Journal of Academic Research and Sciences), 2020)
This research aims at investigating factors affecting enterepeneurship interest in a young entrepreneur program known as KURASA (Kelompok Mahasiswa Wirausaha/Student Enterprise of UNISBA Blitar). This research adopted descriptive qualitative approach. Data were collected through interview, participant observation, and documentation. Then, the student enterprise was selected, and access to informants was built. This research was carried out by collecting data, recording information, comprehending contents, and restoring data. The result shows that young men’s interest in entreprenurship involved in student enterprise was affected by three factors: personality, entrepreneurship education, and environment factors.